A Short Review: Research progress of bovine stem cells - Gao, Y-H; Guan, W-J; Ma, Y-H (Cellular and Molecular Biology, 2015)
All bodies rely on stem cells to grow from a single cell into an adult. Stem cells allow our bodies to build new tissue, such as new muscle when we exercise. Domestic livestock stem cells offer a unique opportunity to study developmental biology, serve as a resource to screen for harmful toxins or lifesaving drugs or even regenerative therapies for a number of diseases. This review provides information on bovine stem cells, emphasizing different sources of stem cells and current methods for isolation and culture of pluripotent stem cells from cattle. We also review the application of bovine stem cell in future.